"My brain freezes and I am blocked again": The subjective experience of post-migration living difficulties influenced by complex posttraumatic stress disorder of Afghan asylum seekers and refugees in Austria. - Jennifer Schiess-Jokanovic; Christine Gösling-Steirer; Viktoria Kantor; Matthias Knefel; Dina Weindl; Brigitte Lueger-Schuster (PLoS ONE)
Background Potentially traumatic experiences and post-migration living difficulties (PMLDs) undoubtedly leave marks on mental health and psychosocial functioning. While PMLDs are recognised as a risk factor for posttraumatic stress disorder and complex posttraumatic stress disorder (described together here as C/PTSD), recent investigations have found that C/PTSD symptoms might also influence the experience of PMLDs. The subjective experience of and coping with PMLDs in the context of C/PTSD symptoms has not yet been explored. Methods Semi-structured, interpreter-assisted interviews exploring the subjective experience of post-migration living difficulties were conducted with treatment-seeking Afghan refugees and asylum seekers (N = 24) and transcribed verbatim. Participants were screened using the International Trauma Questionnaire (ITQ) and allocated to a C/PTSD group or non-C/PTSD group. We analysed the qualitative interviews using content analysis and then compared the results of the two groups. Results Over half of the participants (58.3%) met the criteria for C/PTSD. While the two groups addressed numerous similar themes, the C/PTSD group more frequently mentioned themes associated with C/PTSD symptoms (e.g., intrusions, avoidance, sleep disturbances, affective dysregulation) that influenced their responses to PMLDs. The non-C/PTSD group more often experienced positive emotions such as gratitude and optimism, and showed more active, solution-oriented behaviour as well as positive self-verbalisation. Conclusion To achieve a deeper understanding of PMLDs, post-traumatic psychopathology should be taken into account, as C/PTSD symptoms influence the experience of and coping with PMLDs. The specifics of individual experiences need to be considered in order to promote adaptive coping with PMLDs and to set individual trauma-focused and transdiagnostic treatment targets. In addition, psychological interventions should incorporate psychoeducation to improve the understanding of the impact of C/PTSD on the current experience of PMLDs.